Bibliographic abridgement to work with Local History of Guantánamo - Lilian Pérez-Fermoselle; Marisel Salles-Fonseca; Kobel Guerrero-Muguercia (Universidad de Guantánamo, 2017)
This work happens by the necessity to conceive a bibliographic material about the Local History of Guantánamo that better the treatment of this matter in the classes of History of Cuba that is why is proposed a bibliographic abridgement by means of the Web Site "Mi Matria" as an alternative to elevate the professors' preparation and knowledge that teach this subject. To carry out this research were used methods from the theoretical and empiric method that allowed to confirm the problem object of study. It is supported in the Marxist philosophy from each is took the dialectic materialism and the knowledge theory. In the elaboration of the Web Site containing the bibliographic abridgement were used the Content Manager System Joomla 3.6.5. The Web Site picks up articles, ephemeris, videos, images and a relation of bibliographies; related to the Local History of Guantánamo province. The use of the bibliographic abridgement by means of the Web Site "Mi Matria" in the professors' preparation will favor their level of knowledge about facts, personalities and historical sites of the province making easy the treatment of them in the classes of History of Cuba.